"Olsenella urininfantis", a new bacterial species isolated from a urine sample of a 26-day-old boy suffering from gastroesophageal reflux. (December 2016) - Morand, Aurélie; Chabrol, Brigitte; Fournier, Pierre-Edouard
Abstract: We report here the main characteristics of " Olsenella urininfantis " strain Marseille-P3197 T (CSUR P3197). That strain was isolated from a urine sample of a 26-day-old boy suffering from gastroesophageal reflux.